Tolerance of three grain legume species to transient waterlogging - Malik, Al Imran (AoB Plants, 2015)
Waterlogging reduces the yield of food crops. Tolerance to waterlogging could vary between and within species. This study aimed to quantify tolerance to soil waterlogging in two divergent genotypes of pea (Pisum sativum), two of lentil (Lens culinaris) and a grasspea (Lathyrus sativus) control at germination and during vegetative growth. Following germination, seeds were grown for 14 days in soil waterlogged with the water table 10 mm below the surface, and then by draining the pots and allowing to recover for 21 days—to be compared with 35 days of continuous waterlogging. In both pea and lentil, the pair of genotypes contrasted widely with large-seeded pea genotype Kaspa and lentil genotype Nugget showing higher (2-fold) root porosity and less effect on shoot nitrogen content under waterlogging than the other genotypes (NPE and ATC). During recovery, the same two genotypes—Kaspa pea and Nugget lentil—also recovered better than their smaller-seeded species pairs. Soil waterlogging at 10 mm depth had no significant effect on shoot and root dry mass after 14 days. Root penetration into waterlogged soil was restricted to ∼100 mm depth and its distribution altered for pea and lentil genotypes but not for grasspea. Within the small sample studied, we demonstrated a significant genetic variation in both pea and lentil in tolerance to waterlogging after germination and subsequent recovery for the first time. Screening of additional pea and lentil germplasm for waterlogging conditions is clearly warranted.